2011
DOI: 10.3109/03630269.2011.598985
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Radiological Study of Egyptian β-Thalassemia Intermedia and β-Thalassemia Major Patients: Relation to Complications and Response to Therapy

Abstract: The clinico epidemiological characteristics, frequency of complications, and response to various therapeutic modalities in 80 Egyptian β-thalassemia intermedia (β-TI) patients were compared with 70 β-thalassemia major (β-TM) patients. β-Thalassemia intermedia patients had a higher incidence of left atrium dilatation, right ventricular dilatation and pulmonary hypertension, whereas, β-TM patients showed a higher incidence of left ventricular (LV) dilatation, restrictive LV filling and impaired LV contractility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Reactivation or augmentation of HbF is a possible therapeutic approach for patients with β-TI, and is associated with decreased blood transfusion dependency and improved skeletal deformities and splenomegaly [59,60]. The lower levels of GDF among hydroxyurea treated TI patients compared to untreated counterparts in our study could be explained by the fact that hydroxyurea therapy is associated with suppression of ineffective erythropoiesis [61,62], a condition that causes high-level expression of GDF-15 [11].…”
Section: Discussionmentioning
confidence: 47%
“…Reactivation or augmentation of HbF is a possible therapeutic approach for patients with β-TI, and is associated with decreased blood transfusion dependency and improved skeletal deformities and splenomegaly [59,60]. The lower levels of GDF among hydroxyurea treated TI patients compared to untreated counterparts in our study could be explained by the fact that hydroxyurea therapy is associated with suppression of ineffective erythropoiesis [61,62], a condition that causes high-level expression of GDF-15 [11].…”
Section: Discussionmentioning
confidence: 47%
“…15 Haemolytic anaemia is a known risk factor for PH; a screening study of patients with sickle-cell disease (SCD) in Nigeria showed a PH prevalence of 25% 16 ; a study from Egypt indicates that patients with β-thalassaemia are at risk of PH. 17 Another study from Egypt found a PH prevalence of 9% in patients seropositive for schistosomal antibodies. Ahmed et al 18 from Sudan described 14 consecutive cases of PH with previously treated pulmonary TB and concluded that PH can even occur after resolution of TB, most likely due to persistent lung destruction.…”
Section: Introductionmentioning
confidence: 99%
“…PH with an RVSP>30 mm Hg was present in 4% of long-term survivors in a Zimbabwe cohort of vertically acquired HIV infection 15. Haemolytic anaemia is a known risk factor for PH; a screening study of patients with sickle-cell disease (SCD) in Nigeria showed a PH prevalence of 25%16; a study from Egypt indicates that patients with β-thalassaemia are at risk of PH 17. Another study from Egypt found a PH prevalence of 9% in patients seropositive for schistosomal antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 This condition then lead to hormonal complications and iron overload, which are implicated in bone deformity and loss of bone mineral density (BMD). 6 The resultant outcome of overall bone related physiology could probably lead to the alteration and bone maturity among the children. 8 The gender distribution of the study population indicate the frequency of the male patients was high as compared the female i.e.…”
Section: Discussionmentioning
confidence: 99%